Disseminação da informação em empresas de capital aberto e os processos de mediação da informação - Lopes, Elaine Cristina [UNESP]; Valentim, Marta Lígia Pomim [UNESP]; Almeida Júnior, Oswaldo Francisco de [UNESP] (My University, 2011)
Corporate governance can be understood as management mechanisms that through external and internal controls are going to reduce the distance between minority stakeholders and the control power of the company. In that context, the information management, the information mediation and the information dissemination is very necessary, because the establishment of the good communication, quick, clear and voluntary, in order to establish a confidence climate in the relation of the company with the society, creditors, and collaborators especially with investors. In Brazil, the model created by the stock exchange of São Paulo called of new market , brings in his additional conduct rules purpose to them required by the Brazilian legislation and possessed like base the equity in the handling between part, the transparency in the disclosure of information and responsibility in the installment count. This article presents some considerations about the model of information management and accountability based on legal criteria, in additional standards of information disclosure, and the information mediation process relationship the corporate governança in the business environment.

Governança corporativa pode ser entendida como o conjunto de mecanismos de gestão, que através de controles internos e externos visam reduzir a distância entre acionistas minoritários e o poder de controle da empresa. Nesse contexto, a gestão da informação, a mediação da informação e a disseminação da informação se fazem necessárias, visto que o estabelecimento da boa comunicação, rápida e clara, a fim de estabelecer um clima de confiança na relação da empresa com a sociedade, credores, colaboradores e, especialmente, investidores é extremamente importante. No Brasil, o modelo criado pela Bolsa de Valores de São Paulo chamado de Novo Mercado , traz em seu escopo regras de conduta adicionais às exigidas pela legislação brasileira e possui como base a equidade no tratamento entre partes, a transparência na disseminação de informações e responsabilidade na prestação de contas. Este artigo apresenta algumas considerações acerca do modelo de gestão da informação, os padrões adicionais de disseminação de informações, bem como o processo de mediação da informação relacionado à governança corporativa nesse ambiente empresarial.
Dissemination of information in open capital companies and the process of mediation of information
Keywords: Disseminação da Informação; Mediação da Informação; Processos de Mediação; Gestão da Informação; Governança Corporativa